Application of a Learning Model Based on Local Wisdom to Improve Students Cognitive Abilities in Social Sciences Learning - Sugiantoro; Priyanto, Agustinus Sugeng; Masrukhi; Pahrudin; Kusumawati, Dian (Journal of Social Dynamics and Governance, 2024)
This research examines the effect of integrating local wisdom in social studies learning to improve students’ cognitive abilities. This research explores the instructional and nurturing effects of instilling cultural values within an educational framework. A quantitative approach uses the Design-Based Research (DBR) methodology, which involves the stages of problem identification, design, repeated testing, and evaluation. This research uses a quantitative approach with the Design- Based Research (DBR) method, which focuses on implementing a learning model that incorporates local wisdom, which is applied to 71 students from 4 schools in Sidoarjo Regency. Findings showed significant improvements in students’ cognitive scores, shifting from the reasonably good to the good category after the expanded testing phase. This increase underscores the relevance of culturally enriched education in fostering a deeper understanding of social concepts. This research highlights the importance of using familiar cultural contexts to engage students effectively, which promotes academic success and personal development. Future research should investigate the impact of the model in various socio-cultural settings to validate and expand these findings.